[OP.6A.02] IDEAL CARDIOVASCULAR HEALTH IS INVERSELY ASSOCIATED WITH INCREASED CAROTID-FEMORAL PULSE WAVE VELOCITY IN ITALIAN ADOLESCENTS. THE MACISTE STUDY. (September 2016) - Pucci, G.; Battista, F.; D'Abbondanza, M.; Anastasio, F.; Crapa, M.E.; Sanesi, L.; Troiani, L.; Desantis, F.; Papi, F.; Schillaci, G.
Abstract : Objective: Ideal cardiovascular health (ICH) among adolescents is defined as the optimal levels of three CV risk factors (SBP/DBP < 90°percentile, fasting glucose <100 mg/dL, total cholesterol <170 mg/dL) and four behaviours (body mass index (BMI) <85°percentile, not smoking, presence of >=4 healthy components in diet, moderate or vigorous physical activity at least 1 h/day). We investigated the burden of ICH among Italian adolescents, and its association with arterial stiffness (carotid-femoral pulse wave velocity, cfPWV). Design and method: 307 healthy subjects (mean age 17 ± 2 years, 55% men) attending the Liceo Dontatelli High School, Terni, Italy, were evaluated. Physical activity, dietary and smoking habits were assessed through self-reported questionnaires. Sodium consumption was estimated by single-void second fasting urine samples. Smoking status was confirmed by exhaled carbon-oxyde (pico-smokerlyzer). CfPWV was evaluated by arterial tonometry (SphygmoCor, subtracted distance). For each ICH metric, a score of 2 was also assigned if levels were ideal, 1 if intermediate, and 0 if poor. Results: No one had all 7 ICH metrics; the majority of subjects (76%) had 4 or more ICH metrics; 17 subjects had 6 out of 7 ICH metrics, while 6 subjects had 1 out of 7. Ideal glycemic values were mostly common (99%), while ideal dietary habits the least common (7%). An inverse linear trend in cfPWV was observed over the number of ICH (p for linear trend <0.01, figure). The inverse association between ICH and cf-PWV was observed in females (p < 0.01), but not in men (p = 0.20). When subjects were grouped in tertiles according to ICH score, after adjustment for age and sex, subjects in the lower tertile, compared to upper tertile, showed higher values of cf-PWV (5.1 ± 1.3 m/s vs 4.6 ± 1.8 m/s, p < 0.01), which remained significant after further adjustment for mean BP, height, serum cholesterol, serum glucose, smoking habits, and physical activity (p = 0.02). Conclusions: ICH is relatively uncommon among Italian adolescents, and is inversely related to cf-PWV in females. The potential adverse effects of CV risk factors and unhealthy behaviours on arterial stiffness, an early marker of vascular damage, begins to develop at an early stage of lifespan. Figure. No caption available.